Diabetes - perspectives in drug therapy - Schwanstecher, Mathias; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
Every 5 seconds someone somewhere is diagnosed with diabetes, and every 10 seconds someone dies of it. Even worse, worldwide incidence rates still inexorably escalate. Thus, it is pressing to envisage the extent of the diabetes problem and ensure synergistic approaches aiming in alleviation of its ghastly toll. The chapters of this book report cutting-edge research on molecular events in adiposity and type 2 diabetes, thus opening the way for innovative drug-based therapeutic strategies. It addresses all those who wish to keep in touch with recent developments in the field.
Targeting Type 2 DiabetesSchwanstecher, Christina; Schwanstecher, Mathias; Dual Acting and Pan-PPAR Activators as Potential Anti-diabetic TherapiesHeald, Monique; Cawthorne, Michael A.; Cannabinoids and Endocannabinoids in Metabolic Disorders with Focus on DiabetesMarzo, Vincenzo; Piscitelli, Fabiana; Mechoulam, Raphael; GLP-1 Agonists and Dipeptidyl-Peptidase IV InhibitorsGallwitz, Baptist; SGLT Inhibitors as New Therapeutic Tools in the Treatment of DiabetesKinne, Rolf K. H.; Castaneda, Francisco
Electronic reproduction.
Keywords: Diabetes Mellitus, Type 2 -- Drug therapy; Electronic books